Educating Leaders Who Keep Learning : Christian Education Concepts and Strategies in Preparing Prospective Leaders - Tiurma Barasa (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2021)
The leadership displayed by many leaders today is seen as ineffective and brings significant changes to people's lives. A leadership requires a figure who can manage and manage the system. It makes the effectiveness and efficiency of the system run well towards the expected point. The figure of the leader must be able to work together with those around him, because thus the leader can optimize the existing potential. Leadership is clearly not just talking about position, but rather about influence. Referring to the importance of leadership, the opportunity to learn to be a leader needs to be pursued from an early age. This study aims to prove the influence of understanding the concept of leadership and individual maturity of prospective leaders. This study used descriptive quantitative methods. Before conducting field studies, researchers conducted a literature review on transformative leadership within the framework of Christian education. Respondents were selected as many as 100 students randomly, then analyzed the causal relationship that occurred in it. The results of data processing show that the influence caused by understanding the concept of leadership on the maturity of prospective leaders is 40.9%. Leadership is directed and emphasized on transformative aspects by implementing ennobel, enable, empowering, and encourage.